Hydrothermal characterization of wells GRT-1 and GRT-2 in Rittershoffen, France: Implications on the understanding of natural flow systems in the rhine graben. (January 2017) - Baujard, C.; Genter, A.; Dalmais, E.; Maurer, V.; Hehn, R.; Rosillette, R.; Vidal, J.; Schmittbuhl, J.
Highlights: The ECOGI geothermal project in Rittershoffen, France is presented. Hydraulic data and temperature data are showed. Stimulation results of well GRT-1 is exposed. Convection is investigated. Abstract: An extended description of the implementation of the deep geothermal wells GRT-1 and GRT-2 respectively drilled in 2012 and 2014 in the framework of the ECOGI project is given. These wells located in Rittershoffen (France) offer a unique opportunity to gather high quality datasets on a deep geothermal system in the Upper Rhine Graben at the transition between the Buntsandstein sandstone and the Palaeozoic granite basement. We present the extensive logging and well testing program that was applied and focus on hydraulic and thermal characterization of the targeted deep reservoir. Well architectures of GRT-1 and GRT-2 are described. Temperature logs in both wells are discussed in details. In particular, temperature in the production well GRT-2 is shown to reach 177 °C at 3196 m MD at thermal equilibrium. Production tests of both wells, reservoir development strategy applied in well GRT-1 and circulation test realised between wells are analysed. Productivity and injectivity indexes of GRT-1 and GRT-2 are estimated: Post-stimulation injectivity of GRT-1 and productivity of GRT-2 are respectively estimated to 2.5 l/s/bar and 3.5 l/s/bar. Hydraulic properties of the reservoir are inferred from production tests. Implications for the characterization of the large scale natural hydro-thermal system are discussed.